Taking care of women entrepreneurs in deprived areas ? Supporting business in Politique de la ville - Lorena Clément (GéoProximitéS)
When women’s entrepreneurship is receiving political support from international to local scale, some associations are helping women to set up their own business in disadvantaged neighbourhoods. Entrepreneurship advisors seek to strengthen their capacity for action in a gendered and unequal territorial context. Is this support a form of care ? This question invites us to change the way we look at entrepreneurship and disadvantaged neighbourhoods, by examining micro-local practices of care through a field survey of entrepreneurship support associations operating in Plaine Commune and Nantes Métropole, that uses qualitative methods. The results show that the entrepreneurial and spatial experiences of women in disadvantaged neighbourhoods are structured by gender inequalities. Business support structures aim to reduce these inequalities by reinforcing the autonomy and entrepreneurial legitimacy of these women. While their care practices have an impact at individual level, they do not transform unequal gender relations.